Perceived Stress, Parent-Adolescent/Young Adult Communication, and Family Resilience Among Adolescents/Young Adults Who Have a Parent With Cancer in Taiwan: A Longitudinal Study. Issue 2 (March 2018) - Chen, Chin-Mi; Du, Bao-Feng; Ho, Ching-Liang; Ou, Wei-Jen; Chang, Yue-Cune; Chen, Wei-Ching
Abstract : Background: Family resilience helps family members successfully overcome adversity, for example, chronic disease or unpleasant situations. However, few studies have identified correlates of family resilience among adolescents/young adults having a parent with cancer. Objective: This longitudinal study explored (1) relationships among family resilience, adolescents' perceived stress, and parent-adolescent/young adult communication; (2) trends in family resilience with data collection time; and (3) differences in parent-adolescent/young adult communication by parent gender (ie, father or mother). Methods: Participants were teenagers and young adults (12–25 years) with a parent who had cancer. Data were collected using structured questionnaires at 3 times for 4 to 5 months, with 2 months between each collection. Results: Of 96 adolescent/young adult participants enrolled at T1, only 32 completed all measurements at T3. We found that (1) family resilience was negatively associated with adolescents' perceived stress ( B = −0.35) and positively associated with adolescent/young adult communication with both the father ( B = 0.58) and the mother ( B = 0.36), (2) the degree of family resilience at T3 was significantly lower than at T1 ( B = −4.79), and (3) at all 3 data collection times, the degree of adolescent/young adult communication was higher with mothers than with fathers, whether the mother had cancer or did not have cancer. Conclusions: Family resilience was positively associated with parent-adolescent/young adult communication and negatively related to perceived stress. Family resilience tended to decline with longer parental survival since cancer diagnosis. Implications for Practice: We suggest nursing interventions to reduce adolescent/young adult stress and develop optimal parent-adolescent/young adult communication to enhance family resilience.